2016
DOI: 10.1007/s10646-016-1749-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous honeybee behaviour is altered by persistent organic pollutants

Abstract: The effect of environmental pollutants on honeybee behaviour has focused mainly on currently used pesticides. However, honeybees are also exposed to persistent organic pollutants (POPs). The aim of this laboratory based study was to determine if exposure to sublethal field-relevant concentrations of POPs altered the spontaneous behaviour of foraging-age worker honeybees. Honeybees (Apis mellifera) were orally exposed to either a sublethal concentration of the polychlorinated biphenyl (PCB) mixture Aroclor 1254… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Neonicotinoids target nicotinic acetylcholine receptors (nAChRs) which they bind to and thus excite; this can result in paralysis, convulsions and death (Matsuda et al, 2001). Controlled exposure experiments using honeybees and bumblebees have shown that exposure at comparable concentrations to those found in nectar and pollen can have sublethal effects on learning and memory (Siviter, Koricheva, Brown, & Leadbeater, 2018;Stanley, Smith, & Raine, 2015), cognition and problem solving (Baracchi, Marples, Jenkins, Leitch, & Chittka, 2017;Samuelson, Chen-Wishart, Gill, & Leadbeater, 2016;Williamson & Wright, 2013), motor function (Drummond, Williamson, Fitchett, Wright, & Judge, 2016;Williamson, Willis, & Wright, 2014), foraging performance (Gill & Raine, 2014;Henry et al, 2012;Stanley, Russell, Morrison, Rogers, & Raine, 2016), navigation abilities (Fischer et al, 2014) and the immune system (Brandt, Gorenflo, Siede, Meixner, & Büchler, 2016;Brandt et al, 2017;Di Prisco et al, 2013). Despite the growing interest in the link between neonicotinoid exposure and toxicity to bees, we know little about the molecules and genes through which neonicotinoid action is mediated, or whether neonicotinoids may also affect "off-target" processes that are not mediated by nAChRs.…”
mentioning
confidence: 99%
“…Neonicotinoids target nicotinic acetylcholine receptors (nAChRs) which they bind to and thus excite; this can result in paralysis, convulsions and death (Matsuda et al, 2001). Controlled exposure experiments using honeybees and bumblebees have shown that exposure at comparable concentrations to those found in nectar and pollen can have sublethal effects on learning and memory (Siviter, Koricheva, Brown, & Leadbeater, 2018;Stanley, Smith, & Raine, 2015), cognition and problem solving (Baracchi, Marples, Jenkins, Leitch, & Chittka, 2017;Samuelson, Chen-Wishart, Gill, & Leadbeater, 2016;Williamson & Wright, 2013), motor function (Drummond, Williamson, Fitchett, Wright, & Judge, 2016;Williamson, Willis, & Wright, 2014), foraging performance (Gill & Raine, 2014;Henry et al, 2012;Stanley, Russell, Morrison, Rogers, & Raine, 2016), navigation abilities (Fischer et al, 2014) and the immune system (Brandt, Gorenflo, Siede, Meixner, & Büchler, 2016;Brandt et al, 2017;Di Prisco et al, 2013). Despite the growing interest in the link between neonicotinoid exposure and toxicity to bees, we know little about the molecules and genes through which neonicotinoid action is mediated, or whether neonicotinoids may also affect "off-target" processes that are not mediated by nAChRs.…”
mentioning
confidence: 99%
“…This also includes DMSO. Whether in vertebrates or invertebrates, DMSO effects can be deleterious, with the observation of some cases of cell toxicity [ 42 ], sterility [ 43 ], or neurotoxicity [ 44 ], but also beneficial, with some report of the neutralization or attenuation of pathologies [ 45 ] or with no observed effect [ 46 ]. Our results confirm that DMSO, a solvent used in many studies, even at very low doses, can influence gene and protein expression and that these effects need to be taken into account in differential studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, bees can be used to detect chemical impairment of their habitat by studying various endpoints: mortality (in the case of pesticides to which they are very sensitive); physiological, biochemical, or behavioral changes; and the response of the population distribution to sublethal pollutant toxicity (Dolores Hernando et al 2018). The levels of residues on or within their bodies and the contamination of beehive products reflect the pollutant content of their environment (Porrini et al 2002;Badiou-Beneteau et al 2013;Codling et al 2016;Cousin et al 2019;Drummond et al 2017;El-Saad et al 2017;Hernandez et al 2019).…”
Section: Honeybees and Hive Products As Bioindicators And Bioaccumulamentioning
confidence: 99%
“…Later, honeybees were most commonly used to monitor the levels of pesticides in fields and on vegetables visited by honeybees (Quigley et al 2019;Codling et al 2016;Kasiotis et al 2014;Barganska et al 2018;de Oliveira et al 2016). Several persistent organic pollutants (including explosive residues) originating from industrial and urban activities have also been isolated from bee samples and evaluated (Garcia-Valcarcel et al 2016;Drummond et al 2017;Simic et al 2019;Gómez-Ramos et al 2019). More recently, nanomaterials and nanoparticles have been added to the list of contaminants that honeybees can be used to monitor in the environment (Milivojevic et al 2015;Kojic et al 2020;Hooven et al 2019;Glavan et al 2017).…”
Section: Current Applications Of Biomonitoring Using Honeybeesmentioning
confidence: 99%